2004
DOI: 10.1093/jxb/erh125
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of low-temperature-inducible ribosomal proteins from soybean

Abstract: Three ribosomal protein genes induced by low-temperature treatment were isolated from soybean. GmRPS13 (742 bp) encodes a 17.1 kDa protein which has 95% identity with the 40S ribosomal protein S13 of Panax ginseng (AB043974). GmRPS6 (925 bp) encodes a 28.1 kDa protein which has 94% identity with the 40S ribosomal protein S6 of Asparagus officinalis (AJ277533). GmRPL37 (494 bp) encodes a 10.7 kDa protein which has 85% identity with the 60S ribosomal protein L37 of Arabidopsis thaliana (AF370216). The expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(72 citation statements)
references
References 20 publications
6
64
1
1
Order By: Relevance
“…Unlike the cold responsive CRT/DRE binding factor (CBF) genes that are rapidly and markedly induced within 30 min of cold treatment , the RPL23a paralogs were induced slowly (¸24 h) and accumulated to a maximum of 150-250% of their pre-treatment levels. This result is in agreement with Wndings from soybean (Glycine max) where three ribosomal proteins, RPS6, RPS13 and RPL37, are upregulated within 3-9 days of cold treatment (Kim et al 2004). Additional support is provided by experiments showing upregulation of one or more r-protein transcripts in response to cold treatment of many plant species, including Arabidopsis (Jung et al 2003;Oono et al 2006), canola (Brassica napus, Saez-Vasquez et al 1993, sunXower (Helianthus annuus, Fernandez et al 2008) and trifoliate orange (Poncirus trifoliata, Zhang et al 2005).…”
Section: Discussionsupporting
confidence: 90%
“…Unlike the cold responsive CRT/DRE binding factor (CBF) genes that are rapidly and markedly induced within 30 min of cold treatment , the RPL23a paralogs were induced slowly (¸24 h) and accumulated to a maximum of 150-250% of their pre-treatment levels. This result is in agreement with Wndings from soybean (Glycine max) where three ribosomal proteins, RPS6, RPS13 and RPL37, are upregulated within 3-9 days of cold treatment (Kim et al 2004). Additional support is provided by experiments showing upregulation of one or more r-protein transcripts in response to cold treatment of many plant species, including Arabidopsis (Jung et al 2003;Oono et al 2006), canola (Brassica napus, Saez-Vasquez et al 1993, sunXower (Helianthus annuus, Fernandez et al 2008) and trifoliate orange (Poncirus trifoliata, Zhang et al 2005).…”
Section: Discussionsupporting
confidence: 90%
“…For example, plant ribosomal proteins S14, S15a, S16, L10, L13a, and L30 can be induced by diverse phytohormones, including auxin (32), cytokinin (32,33), and abscisic acid (33), and by stress-inducing stimuli, including heat (32), cold (32,34), and UVB stress (35). Recent analysis of the expression of RP genes and the differential accumulation of RPs in Arabidopsis roots upon phosphate or iron deficiency revealed that these 579 RP genes were associated mainly with abiotic stress responses.…”
Section: Discussionmentioning
confidence: 99%
“…The capacity for thermal acclimation of RNA translation or protein synthesis appears limited, largely relying on production of additional ribosomes (Nomura et al, 1984;Fraser et al, 2002;Storch and Pörtner, 2003;Kim et al, 2004). Such a large difference in ribosomal protein enrichment implies large increases in cellular RNA at lower temperatures, as RNA:protein in ribosomes is constant.…”
Section: Enrichment Patterns At Low Temperaturementioning
confidence: 99%